2014
DOI: 10.1186/s12870-014-0347-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of Flavonoid 3′,5′-hydroxylase from Tea plant (Camellia sinensis): critical role in the accumulation of catechins

Abstract: BackgroundFlavonoid 3′,5′-hydroxylase (F3′5′H), an important branch point enzyme in tea plant flavan-3-ol synthesis, belongs to the CYP75A subfamily and catalyzes the conversion of flavones, flavanones, dihydroflavonols and flavonols into 3′,4′,5′-hydroxylated derivatives. However, whether B-ring hydroxylation occurs at the level of flavanones and/or dihydroflavonols, in vivo remains unknown.ResultsThe Camellia sinensis F3′5′H (CsF3′5′H) gene was isolated from tea cDNA library. Expression pattern analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 40 publications
3
82
0
Order By: Relevance
“…Catechins are highly abundant in tea leaves, and their biosynthesis and accumulation have been extensively studied in this species789. In tea plants, LAR and ANR8, F3′5′H51, and ECGT9 are key downstream enzymes catalyzing the biosynthesis of catechins. Nevertheless, functional characterization of genes for catechin biosynthesis is still limited in tea plants851.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catechins are highly abundant in tea leaves, and their biosynthesis and accumulation have been extensively studied in this species789. In tea plants, LAR and ANR8, F3′5′H51, and ECGT9 are key downstream enzymes catalyzing the biosynthesis of catechins. Nevertheless, functional characterization of genes for catechin biosynthesis is still limited in tea plants851.…”
Section: Discussionmentioning
confidence: 99%
“…In tea plants, LAR and ANR8, F3′5′H51, and ECGT9 are key downstream enzymes catalyzing the biosynthesis of catechins. Nevertheless, functional characterization of genes for catechin biosynthesis is still limited in tea plants851. In this study, qPCR results showed that expression of many upstream flavonoid genes such as CHS, CHI , and F3H , were significantly enhanced in PL compared to SL of ‘YJX’, suggesting the possibility of an enhanced metabolic flux within this part of flavonoid pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Tea is rich in many secondary metabolites associated with tea quality, such as catechin derivatives (catechins), caffeine, and l-theanine [25][26][27]. Catechins that are known as flavan-3-ols are derived from phenylpropanoid and then flux into the flavonoid pathway via the catalyzation of chalcone synthase (CHS) to chalcone [28,29]. Along with the subsequent branches, ECG, EC, EGC, and EGCG, which are the main flavan-3-ols synthetized from catechin isomers, catechins are produced through a suite of crucial enzymes, including: Chalcone isomerase (CHI), flavanone 3-hydroxylase (F3H), flavonoid 3 -hydroxylase (F3 H), flavonoid 3 , 5 -hydroxylase (F3 5 H), dihydroflavonol 4-reductase (DFR), leucoanthocyanidin reductase (LAR), and anthocyanidin reductase (ANR) (Figure 5a).…”
Section: The Effect Of N P and K Starvation On Three Major Secondarmentioning
confidence: 99%
“…After this gene was overexpressed in Populus , a nontargeted GC-MS analysis showed four metabolites closely related to flavonoid biosynthesis ( Table 1 ), and the overexpression of the GbF3′5′H1 gene in Populus promoted the production of three metabolites: 4′,5-dihydroxy-7-glucosyloxyflavanone, epicatechin, and gallocatechin. A functional analysis of F3′5H from Camellia sinensis by Wang et al, (2014) showed that F3′5H plays a critical role in the accumulation of catechins [ 52 ]. Although the results of this study are different from those of Wang et al, (2014), catechin, epicatechin, and epigallocatechin are flavan-3-ols.…”
Section: Discussionmentioning
confidence: 99%